AB0287 Decrease in 14–3–3eta protein levels is correlated with improvement of clinical disease activity in tofacitinib treated early rheumatoid arthritis patients. (12th June 2018) - Shovman, O.; Gilburd, B.; Watad, A.; Amital, H.; Langevitz, P.; Bragazzi, N.L.; Adawi, M.; Pérez, D.; Blank, M.; Biln, N.K.; Marotta, A.; Shoenfeld, Y.
Abstract : Background: 14–3–3η protein is a proinflammatory mediator that may represent a novel diagnostic and prognostic biomarker for rheumatoid arthritis (RA). Objectives: To assess the disease activity parameters and 14–3–3η protein concentrations in serum of early RA patients treated with Tofacitinib. Methods: Paired serum samples from 35 previously non-treated early RA patients (disease onset less than 1 year) receiving Tofacitinib were obtained at baseline and 5 months after the initiation of treatment. Levels of 14–3–3η were measured by JOINT stat 14–3–3η ELISA test kits (Augurex Life Sciences Corp.). The cut-off was defined as 0.19 ng/ml. We investigated the correlation between changes in serum 14–3–3η concentrations and changes in clinical disease activity index (CDAI), simplified disease activity index (SDAI), Disease Activity Score (DAS) 4CRP and DAS4ESR. Results: Increased concentrations of 14–3–3η were found in 57% of the patients at baseline and in 37% of the patients after 5 months of treatment. Mean ±SD baseline 14–3–3η concentrations [4.92±8.86 ng/ml] were significantly higher (p=0.005) than those found following treatment [1.97±4.59 ng/ml]. Statistically significant improvement (p<0.001) of CDAI, SDAI, DAS4ESR and DAS4CRP was achieved after the 5 month of treatment. No correlation was found between absolute 14–3–3η concentrations and parameters of clinical disease activity at both time points. Decrease in 14–3–3η protein levels were highly correlated with improvement in DAS4ESR (r=0.50, p<0.01) and moderately correlated with improvement in CDAI (r=0.32), SDAI (r=0.33), and DAS4CRP (r=0.46, p<0.01). Conclusions: The study demonstrates that decrease in 14–3–3η protein concentrations in RA patients treated with Tofacitinib is correlated with improvement of clinical disease activity parameters. 14–3–3η protein is a useful biomarker for monitoring Tofacitinib therapy. Disclosure of Interest: O. Shovman: None declared, B. Gilburd: None declared, A. Watad: None declared, H. Amital: None declared, P. Langevitz: None declared, N. L. Bragazzi: None declared, M. Adawi: None declared, D. Pérez: None declared, M. Blank: None declared, N. K. Biln Employee of: Augurex Life Sciences Corp, A. Marotta Employee of: Augurex Life Sciences Corp, Y. Shoenfeld: None declared